SISTEM INFORMASI AKADEMIK SUB-SISTEM : UTILITY DAN EPSBED (STUDI KASUS : FAKULTAS TEKNIK UNIVERSITAS HALU OLEO) - Christine Florence Kiswanto; Ika Purwanti Ningrum; Statiswaty Statiswaty (semanTIK, 2016)
Faculty of engineering (FT) is one of  faculty which overshade as a part of  Halu Oleo University and become one of the faculty who award a bachelor degree. Faculty of engineering face the defiance in base academic data processing (utility) and the making of Evaluasi Program Studi Berbasiskan Evaluasi Diri (EPSBED) report. Academic information system (Siakad) is one of the solution who can assist the base academic data processing  and the making of EPSBED report so the multiple times data processing not in the process of. The result of designing and building the Siakad for FT that system is amendable with following Rational Unified Process (RUP) plot and relational database concept is applicable as a concept to design the system’s database.   Keywords— Siakad, utility, EPSBED.